Influence of Employee Well-Being and Mental Health on Employee Performance at BULOG, Cirebon City - Pratama, Fito Ramdhan; Qodriah, Sari Laelatul; Sukartini, Mery (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research investigates the impact of Employee Well-Being and Mental Health on Employee Performance at BULOG in Cirebon City, aiming to examine how these factors affect work outcomes.. Methodology: A quantitative approach was employed, utilizing surveys administered to 49 employees at BULOG Cirebon. The sample size was determined using a saturated sampling technique (census), considering that the total accessible population consisted of only 49 employees, allowing for comprehensive data coverage and minimizing sampling error. The collected data were analyzed using multiple regression to evaluate the relationship between well-being, mental health, and performance. Results: The findings reveal that both Employee Well-Being and Mental Health significantly enhance employee performance. Higher levels of well-being and mental health were associated with increased productivity, better work quality, and greater organizational commitment. Findings: Employee well-being, which includes physical, psychological, and social dimensions, positively influences job satisfaction and performance. Mental health, particularly in terms of stress management, is crucial in mitigating burnout and improving focus. Novelty: This research is distinctive in its investigation of the effects of Employee Well-Being and Mental Health on Employee Performance within BULOG, a government logistics entity in Cirebon, an area that has been relatively under-explored in existing literature. Beyond addressing this contextual gap, the study contributes theoretically by enriching the understanding of how psychological and well-being factors influence performance within public sector organizations, offering insights that extend and refine existing models of employee performance in government logistics settings. Originality: The originality of this study stems from its focus on a public sector organization, BULOG, and its examination of how both physical and psychological aspects of well-being and mental health influence employee performance, offering new insights into human resource management practices in governmental organizations. Conclusion: Fostering a work environment that prioritizes employee well-being and mental health is essential for boosting performance, reducing turnover, and enhancing productivity, especially in high-pressure settings. Type of Paper: Empirical research paper based on quantitative analysis examining the interrelationship between employee well-being, mental health, and performance.